THE INFLUENCE OF JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AT BPJS KETENAGAKERJAAN BRANCH OFFICES ALL MEDAN RAYA AREA - Afriawanto, Denis; Farida Ferine, Kiki (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Human resources are an important factor in an organization or company. In order for management activities to run well, companies must have knowledgeable and highly skilled employees and efforts to manage the company as optimally as possible so that employee performance increases. The type of research used was associative quantitative. The population used was 130 employees and after being scaled down using the Slovin formula to become a sample of 98 employees. The data sources used were primary data sources and data collection was carried out by distributing questionnaires and surveys. The results of this study are job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Commitment can influence job satisfaction and employee performance indirectly.